Stereoelectronic Effects on Dienophile Separation Influence the Diels–Alder Synthesis of Molecular Clefts. Issue 45 (4th December 2017) - Stoermer, Martin J.; Wickramasinghe, Wasantha A.; Byriel, Karl A.; Hockless, David C. R.; Skelton, Brian W.; Sobolev, Alexandre N.; White, Allan H.; Mak, Jeffrey Y. W.; Fairlie, David P.
Abstract : The formal cycloaddition adduct of 1, 4‐benzoquinone with two equivalents of cyclopentadiene is a scaffold with two non‐conjugated alkenes. Both alkenes undergo endo [4+2] cycloaddition with a diene to form a rigid U‐shaped molecular cleft. Here we show experimental, computational and structural evidence that π interactions between the alkenes affect structural rigidity, Diels–Alder reactivity, cleft formation and host–guest capture. Abstract : Five crystal structures show that structural rigidity and π–π interactions strongly influence Diels–Alder [4+2] cycloadditions leading to U‐shaped clefts, one capturing a chloroform molecule within its aromatic enclave.